AL-MABĀHIṠ LAFẒIYYAH: IBĀRAH AL-NAṢ, ISYĀRAH AL-NAṢ, AL-‘ĀM, AL-KHĀS, AL-MUṬLAQ, AL-MUQAYYAD - Madi Madi (IAIN Ambon, 2018)
One of the important elements used as an approach in studying Islamic law is the science of fiqh uṣul. Uṣul fiqh is a science that studies the rules that are used as guidelines in establishing the laws of shari'ah that are 'amaliyah obtained through detailed arguments. Through the rules of uṣul fiqh can be known naṣ-naṣ syara 'and the laws it shows. Among the most important laws of the fiqh are the legal terms of the linguistic terms using the lafẓiyyah method, of which dalalah 'ibārah al-naṣ,' isyārah al-naṣ, al-ām, al-khās, al-muṭlaq and al- muqayyad.